Economic nationalism, network-based coordination, and the market for corporate control: Motives for political resistance to foreign takeovers - Helen Callaghan (Max Planck Institute for the Study of Societies, 2012)
Why does political resistance to foreign takeovers vary across countries and over time? Rational choice accounts of economic nationalism fail to provide an answer. The present article proposes an institutionalist amendment in the 'Varieties of Capitalism' tradition. While politicians everywhere face incentives to favor local stakeholders over anonymous shareholders, stakeholder opposition to foreign takeovers depends on how much of a threat foreign owners pose to network-based coordination. Networks are worth fighting for only where they are actually in use. In so-called outsider systems of corporate governance, including the UK, coordination takes place mainly through market-based mechanisms, and even domestic owners do not rely on networks. Political mobilization is weaker under these conditions. A comparison of Britain and France from the 1970s onward illustrates the argument. – – Warum unterscheidet sich politischer Widerstand gegen ausländische Übernahmen von Land zu Land und im zeitlichen Verlauf? Rational-Choice-Ansätze zum Thema Wirtschaftsnationalismus geben auf diese Frage keine Antwort. Das vorliegende Papier schlägt eine institutionalistische Ergänzung in der 'Varieties-of-Capitalism'-Tradition vor. Während Politiker überall mit dem Anreiz konfrontiert sind, lokale Interessengruppen (Stakeholder) gegenüber anonymen Aktionären zu bevorzugen, hängt der Widerstand der Stakeholder gegen ausländische Übernahmen davon ab, in welchem Maß ausländische Eigentümer eine Gefahr für die netzwerkbasierte Koordination darstellen. Für Netzwerke zu kämpfen lohnt sich nur, wenn diese auch tatsächlich genutzt werden. In sogenannten Outsider-Systemen der Unternehmensführung - darunter Großbritannien - erfolgt die Koordination über marktbasierte Mechanismen und selbst inländische Eigentümer sind nicht auf Netzwerke angewiesen. Unter diesen Umständen fällt die politische Mobilisierung schwächer aus. Ein Vergleich zwischen Großbritannien und Frankreich seit den 1970ern veranschaulicht das Argument.
Keywords: 300